A tale of disaster experience in two countries: Does education promote disaster preparedness in the Philippines and Thailand - Roman Hoffmann; Raya Muttarak (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2015)
Preparing for a disaster can substantially minimize loss and damages from natural hazards. Amongst other socio-demographic determinants, disaster experience and education are found to be key predictors of individual disaster preparedness. This paper explores the pathways through which education enhances disaster preparedness and the interplay between education and experience in shaping preparedness behaviours. Data analysis is based on face-to-face interviews in two disaster-prone countries: the Philippines and Thailand. While education raises the propensity to prepare against disasters, we further find that the effect of education on disaster preparedness is mainly mediated through social capital and disaster risk perception in Thailand but there is no evidence that education is mediated through other observable channels in the Philippines. This in turn suggests that the underlying mechanisms explaining the education effects are highly context-specific. Furthermore, we show that education raises disaster preparedness only for the households that have not been affected by a disaster in the past. One explanation could be that education improves abstract reasoning and anticipation skills such that the better educated undertake preventive measures without needing to first experience the harmful event and then learn later.
Keywords: 300; disaster experience; disaster preparedness; education; mediating factors; Philippines; Thailand